Optimizing the Treatment of Atopic Dermatitis in Infants Using Ursodeoxycholic Acid - O.H. Shadrin; H.A. Haiduchyk (Zaslavsky O.Yu., 2016)
We have determined the advisability of including a suspension of ursodeoxycholic acid into the treatment of atopic dermatitis in infants. It is proved that taking a suspension of ursodeoxycholic acid in 25 infants with atopic dermatitis leads to a positive clinical dynamics of both skin and gastrointestinal manifestations that resulted in a decrease in the area of skin lesions, intensity of itching, sleep normalization and regression of abdominal pain syndrome, possetings.